Post-Fukushima innovation: establishing a regional marine environmental cooperation mechanism in Northeast Asia with global implications - An, Ran; Li, Xuetong; Xie, Yuyan (Frontiers in Marine Science, 2025)
On September 20 2024 China and Japan reached four consensuses on the discharge of Fukushima ALPS-treated water into the sea. This not only eased the tense trade relations between the two states but also provided an important opportunity to build a new type of marine environmental protection cooperation in Northeast Asia. In fact there are multiple environmental protection communication mechanisms in Northeast Asia but there is a lack of truly binding regional environmental protection legal frameworks such as the Espoo Convention the Aarhus Convention. We should take advantage of this opportunity to reach a consensus on cooperation between China and Japan on the discharge of Fukushima nuclear wastewater into the sea combine the actual situation between states in Northeast Asia learn from improve the relatively mature cross-border environmental protection mechanism in Europe rely on the existing regional environmental protection cooperation mechanism available in Northeast Asia to improve upgrade it promote the construction of a new Northeast Asian marine environmental protection legal mechanism contribute Northeast Asian wisdom examples to the world’s marine environmental protection cause.